Pelatihan Penyusunan Media Pembelajaran Interaktif Memanfaatkan Teknologi AI untuk Dewan Guru Bahasa Indonesia Kabupaten Kepahiang - Yanti, Nafri; Noermanzah; Muhammadiansyah, Sandy; Sarina (Journal of Community Empowerment, 2025)
This community service activity aims to improve the competence of Indonesian language teachers in producing interactive learning media through the use of artificial intelligence (AI) technology. The training utilized two main platforms: Magic School AI, which provides over 60 menus to support lesson planning, assessment creation, rubric development, and course guidance for educators; and Classpoint, which is used to create more interactive learning in the classroom. The program targeted teachers who are members of the Indonesian Language Subject Teachers' Conference (MGMP) of Kepahiang Regency Junior High Schools. Evaluation of success was carried out through the administration of pre- and post-test instruments to measure teacher understanding of AI utilization, as well as a survey of participant satisfaction with the training and mentoring. The results of the activity showed an increase in participant knowledge regarding the use of Magic School AI and Classpoint in designing engaging and interactive learning. Participants' responses were generally positive, and the program ran smoothly. This program is expected to be a sustainable step in encouraging teachers to integrate AI technology to create a more effective and enjoyable learning process for students.